Importance of target calorie intake in hospitalized patients - Akbay Harmandar, Ferda; Gömceli, Ismail; Oğuz Yolcular, Başak; Çekin, Ayhan Hilmi (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: To evaluate the feasibility and clinical outcome of a nutritional algorithm based on target calorie intake commenced as enteral nutrition (EN) alone or in combination with supplemental parenteral nutrition (SPN) among hospitalized patients. Materials and Methods: In total, 301 hospitalized patients who were provided with nutritional support, including EN (n=125) or EN+SPN (n=176), due to various medical conditions during their hospitalization were included in this study conducted at Antalya Training and Research Hospital. All the patients were evaluated during their hospitalization under nutritional support until discharge or in-hospital death. Data on the length of stay (LOS) and serum pre-albumin and C-reactive protein (CRP) levels and records for feeding days considering nutritional risk screening (NRS) 2002 scores were collected. Results: Overall, 85.7% of patients achieved the target calorie intake within a median of 4.0 days, while discharge and in-hospital death rates were 58.1% and 41.9%, respectively. Of the 5719 feeding days recorded during follow-up, 1076 (18.8%) days were associated with failure to achieve the target calorie intake with hemodynamic instability (33.3%), procurement problems (33.3%), and oral reluctance (23.0%). Conclusion: Our findings emphasize the role of keeping the intake closer to the target calorie intake and immediate use of SPN whenever full EN fails to achieve the target calorie intake for improving the adequacy of clinical nutrition in the early phase of critical illness. The EN and EN+SPN groups were found to be similar in terms of rates of target achievement, mortality, and discharge, while a lower mortality rate and improved nutritional status were evident in achievers than in non-achievers of the target calorie intake regardless of the type of nutrition. Cite this article as: Harmandar FA, Gömceli İ, Yolcular BO, Çekin AH. Importance of target calorie intake in hospitalized patients. Turk J Gastroenterol 2017; 28: 289-97.